Evaluation of the effects of organic and inorganic amendments on the growth of chilli pepper (capsicum annum l.) plant - George, Tubominayesima Stephen; Onwugbuta-Enyi , Jane Akaja (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
This study examined the effects of poultry, cow dung, household waste and synthetic fertilizer (NPK 10:10:10), on the growth of the chilli pepper (Capsicum annum L.) plant. The experiment was laid out in a Completely Randomized Design (CRD), with four treatments which were replicated four times. The fresh and dry weight of the plant, total fresh matter, proximate contents of fruits and chlorophyll and b contents of the leaves were assessed. Data generated were analyzed using analysis of variance (ANOVA) and the means were compared using the least significant difference (LSD) at a 0.05% level of probability. The result obtained from the study showed that poultry waste produced the highest fresh and dry weight (114g and 58g) respectively, total fresh matter (220g) and chlorophyll (8.5%) content. Cowdung produced the highest phosphorus (P) (5.5/100g) and carotenoid (11.78mg/kg) contents. Plants amended with household waste gave the highest protein (1.4%), crude fibre (4.41%), potassium (K) (243.13mg/100g) and Nitrogen (0.22%) contents. The result suggests that the incorporation of poultry, cow dung and household waste into the soil was better than that with the NPK and the control. Findings, therefore, indicate that the organic manures enhanced the growth and yield performance of Capsicum annum.